Pathogenicity and Mefenoxam Sensitivity of Pythium, Globisporangium, and Fusarium Isolates From Coconut Coir and Rockwool in Marijuana (Cannabis sativa L.) Production - McGehee, Cora S.; Raudales, Rosa E. (Frontiers in Agronomy, 2021)
Oomycetes and fungi were recovered from coconut coir and rockwool substrates where marijuana (Cannabis sativa L. cv. Silver and Citron) plants with root rot and wilt symptoms were grown in a commercial growing facility in Connecticut. The objectives of this study were to identify the isolates collected from these substrates, determine the pathogenicity of the isolates on hemp seedlings in vitro and in vivo, and evaluate the pathogens’ sensitivity to mefenoxam. Pythium and Globisporangium isolates were identified by sequencing the mitochondrially-encoded cytochrome oxidase genes (COI and COII) and Fusarium sp. with the translation elongation factor (EF-1α) region and internal transcribed spacer region (ITS4 and ITS5) genes. Three isolates were identified as Globisporangium irregulare (formerly Pythium irregulare), 21 isolates were Pythium myriotylum, and one was Fusarium oxysporum. All the isolates tested were pathogenic to hemp plants in vitro and in vivo, with disease incidence between 6.7 and 100%. Inoculated plants were smaller by 32% or more compared with the non-inoculated control. On average, hemp plants infected with Pythium myriotylum produced the lowest biomass and relative greenness values. None of the Pythium and Globisporangium isolates were resistant to mefenoxam—all were sensitive to ≥ 5 µg·mL-1 mefenoxam. This is the first report of G. irregulare causing root rot on marijuana and hemp plants. The results of this study provide information about the characteristics of pathogens that can be found potentially in soilless substrates in controlled environment agriculture.